Regulatory impact analysis for good regulation practices: Special reference to public consultation - Mohd Yazid, Abdul Majid; Zuhairah Ariff, Abd Ghadas; Ahmad Shukri, Yazid (2018)
Malaysian Government has introduced a circular, National Policy on the Development and Implementation of Regulation (NPDIR) on 15 July 2013 to eradicate ambush regulation among regulators in Malaysia. The circular which has been issued by the Chief Secretary to the Government was also attached with the Best Practice Regulatory Handbook to facilitate the regulators in Malaysia to develop new or amend existing regulation using Regulatory Impact Analysis (RIA). RIA can only be legitimate and efficient if it is integrated into public consultation procedures. The systematic integration of stakeholders’ views enhances RIA quality by inviting comments from people that will be affected by the regulation. It also helps to improve compliance, as the ownership of the proposed regulation is shared with stakeholders. In order to be effective, consultation requires a number of preconditions. This paper discusses the role and importance of public consultation in RIA and the challenges in implementing public consultation in Malaysia. Date for this papers are derived from primary and secondary sources and interview with relevant parties who are involved with implementing RIA.